2005
DOI: 10.1002/jsfa.2185
|View full text |Cite
|
Sign up to set email alerts
|

The effect of edible eggshell coatings on egg quality and consumer perception

Abstract: Effects of the various coatings (whey protein isolate, chitosan and shellac) on fresh eggs quality were evaluated based on the interior quality and sensory evaluation during 4 weeks of storage. During storage, all egg weights and albumen heights decreased and albumen pH increased. The lowest weight loss (0.75%) was observed in shellac-coated eggs. Eggs coated with chitosan and whey protein also had significantly lower weight loss than uncoated (UC) eggs (p < 0.05). The albumen pH of the UC eggs was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
118
2
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(146 citation statements)
references
References 14 publications
18
118
2
8
Order By: Relevance
“…Even the highest concentration of whey protein coating used (18%) gave higher weight loss of 3.63% after 4th week of storage at ambient condition than observed in this study. In another paper, it was reported that when coatings from whey protein isolate, chitosan and shellac were used, shellac gave least weight loss of 0.75% after 4th week of storage at ambient condition (Caner, 2005b). Bhale et al (2003) also reported that weight loss of chitosan-coated eggs were around 6.8% after 5th week of storage.…”
Section: Weight Changesmentioning
confidence: 99%
“…Even the highest concentration of whey protein coating used (18%) gave higher weight loss of 3.63% after 4th week of storage at ambient condition than observed in this study. In another paper, it was reported that when coatings from whey protein isolate, chitosan and shellac were used, shellac gave least weight loss of 0.75% after 4th week of storage at ambient condition (Caner, 2005b). Bhale et al (2003) also reported that weight loss of chitosan-coated eggs were around 6.8% after 5th week of storage.…”
Section: Weight Changesmentioning
confidence: 99%
“…Stwierdzone ubytki masy w czasie przechowywania są zbieżne z wynikami badań innych autorów, którzy w podobny sposób badali jaja z chowu intensywnego bądź wybiegowego [4,9,23,25,28]. Utrata masy jaja w wyniku przechowywania jest spowodowana ubytkiem wody i dwutlenku węgla przez pory w skorupie [7]. Yilmaz i Bozkurt [28] wykazali związek między ubytkami masy powstającymi w czasie przechowywania a wielkością jaj, co może tłumaczyć najwięk-szy ubytek masy jaj od kur R11.…”
Section: Wyniki I Dyskusjaunclassified
“…According to Caner (2005), weight loss during storage is mainly caused by evaporation of water and loss of CO 2 . Moreover, this reduction in egg weight with storage time may be due to the loss of ammonia, nitrogen, and hydrogen sulfide which are degradation products of the egg organic constituents (SILVERSIDES; BUDGELL, 2004).…”
Section: Egg Weight Loss and Haugh Unitsmentioning
confidence: 99%